Sequential intensive chemotherapy followed by autologous or allogeneic transplantation for refractory lymphoma. Issue 7 (7th June 2021) - Orfali, Nina; Jhanwar, Yuliya; Koo, Calvin; Pasciolla, Michelle; Baldo, Maria; Cuvilly, Edwidge; Furman, Richard; Gergis, Usama; Greenberg, June; Guarneri, Danielle; Hsu, Jing-Mei; Leonard, John P.; et al.
Abstract: We evaluate the safety of bendamustine as a bridge to stem cell transplantation (SCT) in patients with relapsed/refractory lymphoma and residual disease after salvage therapy. Thirty-four subjects without complete responses (CR) received bendamustine 200 mg/m 2 /day for 2 days followed 14 days later by SCT. Sixteen subjects in partial remission (PR) with maximal FDG-PET SUVs ≤8 prior to bendamustine received autologous SCT, while 13 with suboptimal responses were allografted. Five subjects did not proceed to transplant. No bendamustine toxicities precluded transplantation and no detrimental effect on engraftment or early treatment-related mortality (TRM) was attributable to bendamustine. At 1 year, 75% of auto-recipients and 31% of allo-recipients were alive with CR. Two subjects in the autologous arm developed therapy-related myeloid neoplasia (t-MN). In conclusion, a bendamustine bridge to SCT can be administered without early toxicity to patients with suboptimal responses to salvage chemotherapy. However this approach may increase the risk of t-MN. (NCT02059239). Supplemental data for this article is available online at here .